2020
DOI: 10.1186/s12936-020-3141-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum pre-erythrocytic stage vaccine development

Abstract: Worldwide strategies between 2010 and 2017 aimed at controlling malarial parasites (mainly Plasmodium falciparum) led to a reduction of just 18% regarding disease incidence rates. Many biologically-derived anti-malarial vaccine candidates have been developed to date; this has involved using many experimental animals, an immense amount of work and the investment of millions of dollars. This review provides an overview of the current state and the main results of clinical trials for sporozoite-targeting vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 174 publications
0
33
0
Order By: Relevance
“…The merozoite stage of the parasite that the sporozoite transforms itself into, and emerges from the hepatocytes 7–10 days later causing clinical malaria, is unrecognized by the RTS, S-induced antibodies or T cell responses. Preventing any sporozoites from reaching the liver in the short window of opportunity available appears a practically difficult task even with strong circulating antibody responses [ 30 ]. In addition, waning CSP-specific immune responses from RTS, S/AS01 vaccination is a significant shortcoming.…”
Section: Subunit Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The merozoite stage of the parasite that the sporozoite transforms itself into, and emerges from the hepatocytes 7–10 days later causing clinical malaria, is unrecognized by the RTS, S-induced antibodies or T cell responses. Preventing any sporozoites from reaching the liver in the short window of opportunity available appears a practically difficult task even with strong circulating antibody responses [ 30 ]. In addition, waning CSP-specific immune responses from RTS, S/AS01 vaccination is a significant shortcoming.…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…When administered with the adjuvants Abisco-100 and Matrix-M, R21 elicited protection against the Pf CSP-transgenic P. berghei sporozoite challenge [ 48 ]. A clinical trial using R21 with the AS01 adjuvant was well-tolerated and induced a strong anti-CSP antibody response [ 30 ]. R21 is now under evaluation in Phase 1/2a clinical trials [ 49 ].…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…While we agree that efforts to find and introduce new candidate pre-erythrocytic malaria vaccines are warranted, we disagree with the statement of Molina-Franky and colleagues [ 1 ] that none of these approaches has led to promising results regarding an effective control of the disease. It is indeed our opinion that the results available today for RTS,S/AS01, and based on at least 28 clinical Phase I, II and III studies [ 2 ] (and not five studies as suggested in Table 1 of the paper) do indicate the potential of this vaccine to provide substantial public health benefit.…”
Section: Main Textmentioning
confidence: 60%
“…P36 interacts with hepatocyte's extracellular receptor EphA2 to create a protective parasitophorous vacuole that facilitates hepatocyte invasion [100]. PfSPZ vaccine prevents the sporozoites reaching the liver and infecting hepatocytes [101], and is currently undergoing phase III clinical trial [102]. PfSPZ vaccine was designed to have a live, whole sporozoite that is radiated-attenuated.…”
Section: Pfspzmentioning
confidence: 99%
“…Furthermore, efficacy varied by locations. For example, in Mali, 29% efficacy was reported in subject who were exposed to heterologous strain; whereas in CHMI, 83% of subjects were found to be protected from exposure to heterologous strains [102]. Further studies are needed to compare efficacy among different geographical or transmission settings.…”
Section: Pfspzmentioning
confidence: 99%